Peritoneal Carcinomatosis Targeting with Tumor Homing Peptides - Simón-Gracia, Lorena (Molecules, 2018)
Over recent decades multiple therapeutic approaches have been explored for improved management of peritoneally disseminated malignancies—a grim condition known as peritoneal carcinomatosis (PC). Intraperitoneal (IP) administration can be used to achieve elevated local concentration and extended half-life of the drugs in the peritoneal cavity to improve their anticancer efficacy. However, IP-administered chemotherapeutics have a short residence time in the IP space, and are not tumor selective. An increasing body of work suggests that functionalization of drugs and nanoparticles with targeting peptides increases their peritoneal retention and provides a robust and specific tumor binding and penetration that translates into improved therapeutic response. Here we review the progress in affinity targeting of intraperitoneal anticancer compounds, imaging agents and nanoparticles with tumor-homing peptides. We review classes of tumor-homing peptides relevant for PC targeting, payloads for peptide-guided precision delivery, applications for targeted compounds, and the effects of nanoformulation of drugs and imaging agents on affinity-based tumor delivery.